High temperature transesterification of soybean oil with methanol using manganese carbonate as catalyst - Wan Liang (Chemical Industry and Chemical Engineering Quarterly, 2018)
The manganese carbonate catalyst, prepared by precipitation method, was used in transesterification of soybean oil under subcritical condition of methanol. Catalyst samples were characterized by X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS). The triacylglycerol (TAG) conversion and fatty acid methyl esters (FAME) yield were determined using high performance liquid chromatography (HPLC). The transesterification was realized for 1 h using various working conditions: 0-3 wt.% of catalyst (based on the mass of oil), the mole ratio of methanol to oil from 13:1 to 27:1 and temperature ranging from 393 to 473 K. A maximum TAG conversion of 98.1% could be obtained at the optimal reaction conditions: 2 wt.% of catalyst, methanol/oil mole ratio of 21:1, for 1 h in a batch reactor at 453 K. Kinetic analysis showed that the model based on mass transfer and chemical reaction at the catalyst surface confirmed the experimental data. Using that kinetic expression, the effect of continuous transesterification was proposed and verified by a 360-h long realized experiment in a laboratory packed-bed reactor (PBR). Slow deactivation of the catalyst was caused by leaching of Mn in both biodiesel and glycerol phases and by blocking the active sites of the catalyst with organic compounds.